Students’ Trust and Their Educational Trajectory after Graduation - I. S. Kuznetsov (Высшее образование в России)
The article is devoted to the role of students’ trust in shaping their educational trajectory after graduation. In particular, the question is how students’ trust in the actors of higher education (peers, teachers and university management) is related to their intention to continue their education in the specialty received after graduating from a bachelor’s or specialist’s degree. The nature of trust refers not only to the psychological characteristics of a person, but also finds its roots in social relations. When studying educational trajectories this hallmark of trust makes it possible to shift the focus from socio-economic, institutional, gender, and psychological factors that are regularly in the field of researchers’ attention to relational ones, which appear relatively rarely in their field of interest. The work uses data from a sociological survey of students of Russian universities. The results obtained are that students’ trust in university management, in contrast to their trust in other actors, is the most significant indicator that they will continue their education in their specialty after graduation. Students’ trust in peers and teachers are less stable factors. In addition, the addressee of trust, rather than the radius, is more important for students to decide whether to continue their education in their specialty after graduation.